Una proposta per una didattica significativa - Fiorentini, Carlo (Studi sulla Formazione/Open Journal of Education, 2021)
We are going to introduce the epistemological, psychological, pedagogical and didactic aspects related to a scientific teaching approach in the First Cycle effectively able to overcome the trasmissive and notional method widely diffused among Italian schools. The proposed methodological model of the five phases provides after observation, as a second phase, the most innovative aspect, the individual written verbalization.